Impact of Frailty and Cervical Radiographic Parameters on Postoperative Dysphagia Following Anterior Cervical Spine Surgery - Asada, Tomoyuki; Singh, Sumedha; Maayan, Omri; Shahi, Pratyush; Singh, Nishtha; Subramanian, Tejas; Araghi, Kasra; Korsun, Maximilian; Tuma, Olivia; Pajak, Anthony; Lu, Amy; Mai, Eric; et al. (Spine (Philadelphia, Pa. 1976), 2024)
Retrospective review of a prospectively collected registry. The purpose of the present study was to investigate the impact of frailty and radiographical parameters on postoperative dysphagia after anterior cervical spine surgery (ACSS). There is a growing body of literature indicating an association between frailty and increased postoperative complications following various surgeries. However, few studies have investigated the relationship between frailty and postoperative dysphagia after anterior cervical spine surgery. Patients who underwent anterior cervical spine surgery for the treatment of degenerative cervical pathology were included. Frailty and dysphagia were assessed by the modified Frailty Index-11 (mFI-11) and Eat Assessment Tool 10 (EAT-10), respectively. We also collected clinical demographics and cervical alignment parameters previously reported as risk factors for postoperative dysphagia. Multivariable logistic regression was performed to identify the odds ratio (OR) of postoperative dysphagia at early (2-6 weeks) and late postoperative time points (1-2 years). Ninety-five patients who underwent ACSS were included in the study. Postoperative dysphagia occurred in 31 patients (32.6%) at the early postoperative time point. Multivariable logistic regression identified higher mFI-11 score (OR, 4.03; 95% CI: 1.24-13.16; P =0.021), overcorrection of TS-CL after surgery (TS-CL, T1 slope minus C2-C7 lordosis; OR, 0.86; 95% CI: 0.79-0.95; P =0.003), and surgery at C3/C4 (OR, 12.38; 95% CI: 1.41-108.92; P =0.023) as factors associated with postoperative dysphagia. Frailty, as assessed by the mFI-11, was significantly associated with postoperative dysphagia after ACSS. Additional factors associated with postoperative dysphagia were overcorrection of TS-CL and surgery at C3/C4. These findings emphasize the importance of assessing frailty and cervical alignment in the decision-making process preceding ACSS.